(untitled) (The Review of Diabetic Studies, 2023)
BACKGROUND: Oxidative stress plays an important role in the development of diabetic cardiomyopathy. Alpha-lipoic acid (ALA) is a powerful antioxidant that may have a protective role in diabetic cardiac dysfunction. AIM: We investigated the possible beneficial effect of alpha-lipoic acid on diabetic left ventricular (LV) dysfunction in children and adolescents with asymptomatic type 1 diabetes (T1D). SUBJECTS AND METHODS: Thirty T1D patients (aged 10-14) were randomized to receive insulin treatment (n = 15) or insulin plus alpha-lipoic acid 300 mg twice daily (n = 15) for four months. Age and sex matched healthy controls (n = 15) were also included. Patients were evaluated with conventional 2-dimensional echocardiographic examination (2D), pulsed tissue Doppler (PTD), and 2-dimensional longitudinal strain echocardiography (2DS) before and after therapy. Glutathione, malondialdhyde (MDA), nitric oxide (NO), tumor necrosis factor-alpha (TNF-alpha), Fas ligand (Fas-L), matrix metalloproteinase 2 (MMP-2), and troponin-I were determined and correlated to echocardiographic parameters. RESULTS: Diabetic patients had significantly lower levels of glutathione and significantly higher MDA, NO, TNF-alpha, Fas-L, MMP-2, and troponin-I levels than control subjects. The expression of transforming growth factor beta (TGF-beta) mRNA in peripheral blood mononuclear cells was also increased in diabetic patients. Significant correlations of mitral e’/a’ ratio and left ventricular global peak systolic strain with glutathione, MDA, NO, TNF-alpha, and FasL were observed in diabetic patients. Alpha-lipoic acid significantly increased glutathione level and significantly decreased MDA, NO, TNF-alpha, Fas-L, MMP-2, troponin-I levels, and TGF-beta gene expression. Moreover, alphalipoic acid significantly increased mitral e’/a’ ratio and left ventricular global peak systolic strain in diabetic patients. CONCLUSION: These findings suggest that alpha-lipoic acid may have a role in preventing the development of diabetic cardiomyopathy in type 1 diabetes.